Analysis of Language Errors in The Use of Indonesian Language on Social Media - Gabriella Dianra; Siti Enik Mukhoiyaroh Bambang (BRIGHT VISION, 2026)
The use of Indonesian on social media is currently still frequently encountered with language errors, both in posts and user comments. This phenomenon occurs because language use on social media tends to be more casual, fast-paced, and does not always adhere to proper Indonesian language rules. This study aims to analyze the forms of language errors in the use of Indonesian on social media. This study uses a qualitative approach with a language error analysis design in linguistic studies. The research data sources were posts and comments on public social media platforms like Instagram and TikTok, accessed between January and February 2026. The research data consisted of words, phrases, and sentences containing language errors. Data collection techniques were carried out through listening and documentation techniques, while data analysis techniques were carried out through the stages of data reduction, data classification, data presentation, and drawing conclusions. The results of the study indicate that the language errors found included errors in spelling, phonology, morphology, syntax, semantics, diction, and the use of ineffective sentences. These errors are generally influenced by the habit of using casual language, the use of abbreviations, and the influence of slang in digital communication. Therefore, public awareness is needed to pay more attention to the use of proper Indonesian on social media.